Dynamic failure of fibre-metal laminates under impact loading - experimental observations - Li, Xin (SAGE Publications Ltd., 2016)
The dynamic failure of fibre metal laminates was investigated experimentally. A projectile of hemispherical head with a diameter of 36.5 mm was used to impact the fibre metal laminate panels. Three types of woven fibre fabrics (Basalt, S2-glass and Kevlar-29) were used to reinforce the aluminum sheets. Tests on these fibre metal laminate panels were conducted by using an aerodynamic gun with the impact velocity ranging from 20.6 m/s to 42.8 m/s. Different deformation/failure modes of fibre metal laminates were obtained by varying the impact energy. The failure mechanisms of composite layers were examined by the field emission scanning electron microscope. The results showed that before the fibre metal laminate panels were penetrated, the global deformation increased with the impact velocity. However, evident reduction of global deformation can be observed after penetration occurred. Damages of fibre metal laminate panels such as tearing of aluminum ply, fibre fracture, matrix cracks and debonding/delamination were observed around the impact region. The results indicate that basalt reinforced aluminum laminates perform well in terms of impact resistance and offer significant potential in engineering applications.